Dolichyl-Phosphate Alpha-N-Acetyl Glucosaminyl Transferase (DPAGT1); A Target Enabling Package - Carpenter, E (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. The ER integral membrane enzyme dolichyl-phosphate alpha-N-acetyl glucosaminyl phosphotransferase (DPAGT1) catalyses the first step in the synthesis of the oligosaccharide-P-P-dolichol unit which provides the glycans structure for N-glycosylation of proteins. Mutations in DPAGT1 cause two muscle weakness conditions, limb-girdle congenital myasthenic syndrome (CMS) and congenital disorder of glycosylation type 1j (CDG1j). DPAGT1 overexpression has also been implicated in oral cancer. We have produced and solved structures of this integral membrane enzyme, DPAGT1 with the V264G mutation found in a patient with CMS, and complexes with a 50 nM inhibitor, tunicamycin. We have developed enzymatic activity and thermostability assays which have allowed us to assess the activity and stability of DPAGT1 mutants and the effect of small molecules. There are > 20 DPAGT1 associated missense variants in patients with CMS and CDG1j. We have mapped these mutations to the structure, and we will used the assays described here to assess how the activity and stability of DPAGT1 is affected by these missense variants.